Long-standing persistent atrial fibrillation with low coronary flow reserve is associated with unnecessary coronary angiography. (3rd October 2022) - Daniels, F; Elvan, A; Beemsterboer, I T A; Mouden, M
Abstract: Background/Introduction: Atrial fibrillation (AF) is associated with an increased risk of myocardial infarction. Myocardial perfusion imaging (MPI) is well-established for the diagnosis of coronary artery disease (CAD) and risk-stratification in sinus rhythm (SR) patients. Purpose: The aim of this study was to determine the impact of AF and coronary flow reserve (CFR) on revascularization in patients undergoing positron emission tomography (PET) MPI. Methods: 680 patients without a known history of CAD were included. 226 paroxysmal AF (PAF) and 114 long-standing persistent AF (LSPAF) patients were identified from a single-center prospective PET MPI registry and propensity matched in a 1:1 ratio to SR patients. The main indications for PET MPI were chest pain and dyspnea. Follow-up was obtained for downstream referral for invasive coronary angiography (CAG) and the occurrence of myocardial infarction (MI) or coronary revascularization. Results: Compared with PAF, LSPAF patients were older (p=0.011) and more frequently male (p=0.031), with no significant differences in prior medical history and cardiac risk factors. The number of abnormal scans (infarction or ischemia) did not differ significantly between SR and AF, respectively 22.1% and 18.5% (p=0.253). The frequency of downstream CAG was comparable between the groups (p=0.298), with a significantly higher yield of obstructive CAD in the SR group as compared to PAF and LSPAF groups (63% vs 42% vs 36%, p=0.007). A low CFR (defined as CFR below the median of 2.4) in patients with SR showed significantly more revascularization compared with PAF and LSPAF (p<0.001), although more patients with LSPAF and low CFR underwent CAG (p<0.001). In patients with low CFR referred for CAG, the overall prevalence of obstructive coronary artery disease on CAG was 62%, with 30% for LSPAF, 52% for PAF and 78% for SR. There were no significant differences between SR, PAF and LSPAF in the occurrence of MI during a mean follow-up of 36 months (p=0.256). Conclusion: A low CFR was only associated with a higher incidence of revascularization in patients with SR. Among patients with low CFR, LSPAF patients have the highest number of unnecessary CAGs as compared with SR and PAF. Funding Acknowledgement: Type of funding sources: None.